Application of Multimedia Technology (MTA) in The Qiraat Course: A Study on Darul Quran Students, Jakim - Hayati Hussin; Abd Rahman Abd Ghani; Abdul Rahim Ahmad (Human Resource Management Academic Research Society, 2024)
Vol. 12(1) 2023, Pg. 1283 - 1294